Employee involvement, job satisfaction, and in-role performance - Nikodemus Hans Setiadi Wijaya; Diaz Haryokusumo; Muhammad Dian Akbar (Diponegoro International Journal of Business, 2021)
This study examines the relations among employee involvement, job satisfaction, and in-role performance. Job satisfaction is posited as a mediator. A total of 102 respondents filled out a self-administrated survey. The hierarchical regression analysis was performed to test the direct influence hypotheses. To carry out the mediation test, the procedures proposed by Baron and Kenny and the Sobel Test to strengthen were both used. It was found that the influence of employee involvement variables was positive on job satisfaction and in-role performance. Results also showed a positive of job satisfaction on in-role performance. Job satisfaction partially mediated the relationship between employee involvement and in-role performance.  Implications of the findings, implications, and limitations are discussed.